Pemanfaatan Financial Technology Dalam Peningkatan Efektifitas Pemasaran di Era Digital - As-Syahri, Hidayatullah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In the digital era, financial technology (fintech) has become one of the main pillars in the transformation of the global economy, particularly in the marketing sector. This research aims to review existing literature on the utilization of fintech to enhance marketing effectiveness. By conducting a literature review, this study identifies various ways in which fintech influences marketing strategies, including digital payments, consumer data analysis, and marketing platform integration. The findings indicate that fintech not only facilitates financial transactions but also provides valuable insights that can be used to develop more effective and efficient marketing strategies. Additionally, fintech enables better personalization in marketing, enhances customer experience, and expands market reach through internet-based technologies. This research also discusses the challenges faced in implementing fintech in the marketing sector and provides recommendations for further research. In conclusion, fintech offers various benefits in improving marketing effectiveness, but challenges such as data security and technology adoption must be addressed to maximize fintech's potential. Understanding and adapting to the latest trends in fintech will be key for companies to remain competitive in an ever-evolving market.